2021
DOI: 10.1177/17579759211016802
|View full text |Cite
|
Sign up to set email alerts
|

Scoping health literacy in Latin America

Abstract: Studies evaluating the influence of health literacy on patient behavior and outcomes suggest a positive relationship between health literacy and health knowledge, health behaviors, and health status. In Latin American countries, studies assessing health literacy are few, regional, and demonstrate considerable variation, with reported rates of adequate health literacy ranging from 5.0% to 73.3%. In this paper, we examine and explore the state of health literacy and efforts to promote it in Latin America. Key ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Recently, [ 52 ] found that the level of education can influence the dietary profile of the population of London, United Kingdom, in three ways: (i) low education is linked to diets rich in carbohydrates and low in fiber; and (ii) low education is also associated with higher consumption of sweets and red meat, and high education is associated with higher consumption of fruits, vegetables, and fish. In Latin America, it was observed that the main factors that hinder the state of health conditions in this population are: socioeconomic inequality (e.g., low education), social/geographical isolation and cultural barriers, and linguistic and political, which mainly affect indigenous and other populations living in rural areas [ 53 ]. Considering Brazilian Amazon populations, studies in riverside populations of the Pará (Tapajós River and Tucuruí Lake) and Amazonas (Negro River and Solimões River) states demonstrate that the profile or status of educational and bad habits (food and health) of riverine people are risk factors for the development of the metabolic syndrome and cardiometabolic diseases [ 21 , 27 , 48 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, [ 52 ] found that the level of education can influence the dietary profile of the population of London, United Kingdom, in three ways: (i) low education is linked to diets rich in carbohydrates and low in fiber; and (ii) low education is also associated with higher consumption of sweets and red meat, and high education is associated with higher consumption of fruits, vegetables, and fish. In Latin America, it was observed that the main factors that hinder the state of health conditions in this population are: socioeconomic inequality (e.g., low education), social/geographical isolation and cultural barriers, and linguistic and political, which mainly affect indigenous and other populations living in rural areas [ 53 ]. Considering Brazilian Amazon populations, studies in riverside populations of the Pará (Tapajós River and Tucuruí Lake) and Amazonas (Negro River and Solimões River) states demonstrate that the profile or status of educational and bad habits (food and health) of riverine people are risk factors for the development of the metabolic syndrome and cardiometabolic diseases [ 21 , 27 , 48 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, there has been an increase in new HIV diagnoses among newly arrived people born in Latin America or Caribbean in Australia. [32][33][34] Because of cultural factors, stigma, and discrimination, people from these regions may have limited access to sexual health information and resources [35][36][37] ; important sexual health messages and education can be delivered to these clients via SHAVE, and they can review these resources in their private own time to reduce embarrassment and shame.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs are typically not effective in treating fibromyalgia pain because they have peripheral rather than central mechanisms of action [54][55][56]. Since many are available over-the-counter, they may be taken by patients trying to seek pain relief, but are generally not effective.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%